Research priorities for mental health in schools in the wake of COVID-19. Issue 5 (29th November 2021) - Barker, Rhiannon; Hartwell, Greg; Bonell, Chris; Egan, Matt; Lock, Karen; Viner, Russell M
Abstract : Children and young people (CYP) have suffered challenges to their mental health as a result of the COVID-19 pandemic; effects have been most pronounced on those already disadvantaged. Adopting a whole-school approach embracing changes to school environments, cultures and curricula is key to recovery, combining social and emotional skill building, mental health support and interventions to promote commitment and belonging. An evidence-based response must be put in place to support schools, which acknowledges that the mental health and well-being of CYP should not be forfeited in the drive to address the attainment gap. Schools provide an ideal setting for universal screening of mental well-being to help monitor and respond to the challenges facing CYP in the wake of the pandemic. Research is needed to support identification and implementation of suitable screening methods.